Aspek Hukum Bisnis Dan Perlindungan Konsumen Dalam Bisnis Digital (Transaksi Online) - Adinda Nurul Hanafi; Afifah Salsabilah Okadri; Dinda Mardhatillah; Resiahati Putri (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2023)
This study examines the legal aspects of business and consumer protection in digital business (online transactions). The research aims to provide a detailed description of the social phenomena related to consumer protection in digital business. The findings indicate that consumer protection in digital business is still ineffective, with consumers experiencing difficulties in filing claims and receiving compensation if errors occur in online transactions. The legal challenges of digital business also remain unresolved, including data and privacy protection, electronic transactions and digital signatures, and intellectual property rights. The study suggests that a clear and effective legal framework, as well as better consumer protection, are necessary to address these issues.